Integrating gamification in design research: a pedagogical approach for design education in India - Srivastava, Ishi; Sachdeva, Heena; Tyabji, Shirali (Springer Nature - Discover Education, 2025)
Gamification is gaining prominence in design education, offering innovative methods to enhance student engagement and develop critical competencies such as collaboration, creativity, and problem-solving. This study investigates the integration of gamification into a first-year Design Research course at ATLAS SkillTech University, Mumbai, India, over two academic years—Fall 2023 and Fall 2024. The objective was to address the challenges of traditional pedagogies, which often struggle to engage students in research-focused courses, by creating an immersive, student-centric learning experience. A mixed-method approach was employed, combining surveys and personal interviews with 259 respondents, including students and faculty. Specific gamification elements were incorporated into the curriculum to teach the research process, prioritizing active participation and engagement. The revamped course was evaluated to understand the impact of these elements on learning outcomes. Results indicated significant improvements in student engagement, peer collaboration, and creativity, highlighting the potential of gamification to transform research-based learning in design education. Specifically 46% of students found gamified elements such as integration of snakes and ladder engaging. While 30% of the students found the game very engaging indicating that 76% responded positively to the approach. These findings underscore the significance of integrating gamified strategies to meet the diverse needs of modern learners and enhance educational innovation. The study advocates for gamification as a tool to prepare future designers for a rapidly evolving industry while enriching the discourse on adaptive pedagogical practices.
ISDI
Keywords: Gamification; pedagogical practices; Design Research